Economics and safety of tall building design based on 2D frame analysis - Leung, Chun-wai; Worsak Kanok-Nukulchai; Pichai Nimityongskul; Ueda, Tamon; The Government of Japan (Bangkok : Asian Institute of Technology, 1990)
Many three-dimensional multistory tall buildings are analyzed using simplified 2D frame analytical techniques and plane frame computer programs in practice. The accuracy of these design techniques may not be sufficient to ensure an economics and safety design because important factors are neglected in the techniques. To evaluate the economics and safety of tall building design based on 2D frame analysis, tall building models with varying building parameters are tested by 2D frame analysis and more rigorous by 3D analysis. A real case study of tall building in Thailand are tested also. The results show that for frame building system without shearwall, a design based on simplified 2D frame analysis under static or dynamic load is acceptable. Coupled frame-shearwall building will be over-designed if results of 2D analysis are used especially at lower stories for building which basically deform in bending mode and of which the number of stories is above twenty five. Tall building designed from results of a three-dimensional analysis can very well resist the worst loading condition as expected. Building design based on 2D frame analysis is partly over-designed and partly unsafe
A thesis submitted in partial fulfillments of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1990
Keywords: Tall buildings; Structures, Theory of